Physical attributes of the soil in an area under Forage Palm management in the Agreste of Alagoas - Costa, Julio César Calixto; Santos, Cícero Gomes dos; Melo, Raví Emanoel de; Silva, Lucas Santos da; Santos, Darlan Silva dos (Revista Ambientale, 2024)
The objective was to evaluate soil density (Ds) and penetration resistance (RP) in an experimental area with forage palm management. The study was conducted in an experimental area belonging to the Federal University of Alagoas - Arapiraca Campus. To determine the Ds, undeformed samples were collected at three points within the plot, each point with three different depths (0-10; 10-20 and 20-30 cm). To determine the PR, the impact penetrometer was used at depths of 0-60 cm. For comparison purposes, samples were collected in a native forest area. The data were submitted to analysis through the statistical program R and Tukey test at 1 and 5% probability. Ds ranged from 1.59 to 1.63 g cm-3, not differing significantly. The lowest densities were obtained in the surface layer, influenced by the contribution of organic matter and greater presence of roots. In all depths evaluated, the Ds values were lower for the native forest area. In relation to PR, the values gradually increased up to the first 20 cm of depth for most treatments, reflecting the influence that the non-soil revolution causes in the most superficial layers. Therefore, Ds did not differ significantly. The 0-10 cm layer showed the lowest Ds values. The native forest showed the lowest Ds values at all depths when compared to the managed area. PR gradually increased to the first 20 cm of depth for most of the treatments analyzed.